👤

Introduceti factorii sub radical,punand conditiile necesare care se impun:
x√2=

-3a√5=

3x²√2=

-4a²√15=

x√6x=

b√6a² supra b=

-6x³√2 supra x³=

-o,(6)a²b√3b=


formule-
b≥0,a√b=a²b
a>0,a√b=√a²b


Răspuns :

daca x ≥ 0          ⇒  x√2 = √x²·√2 = rad ( 2x² ) 
daca a ≥0               -3a√5 = - √9·√a²·√5 =  - rad( 45a²)
 3x²√2 = √9·√x⁴√2  = rad ( 18x⁴ )
- 4a²√15  = - √16√a⁴√15  = -  rad ( 16 ·15a⁴ ) = - rad( 240a⁴ )
x≥ 0                 ;         x√6x = √x²·√6x  =  rad(x² ·6x ) = rad( 6x³ )
b >0                ;  b√6a²/b =  rad( b²·6a² / b ) = rad( 6a²b) 
x > 0               ;  -6x³√2 /x³  = - rad( 6²·x⁶ ·2 / x³ ) = - rad( 72x³ )
a, b ≥ 0           ;    0,(6) = 6 / 9  = 2 / 3 
                          - 2 /3  · a²b√3b  = -  rad ( 2² ·a⁴b²· 3b  / 3² ) 
                     = - ( 4·a⁴b³ / 3)  
x√2=√x²*2=√2x²
-3a√5=√(-3a)²*5=√9a²*5=√45a²
3x²√2=√(3x²)²*2=√9x⁴*2=√18x⁴
-4a²√15=√(4a²)²*15=√16a⁴*15=√240a⁴
x√6x=√x²*6x=√6x³
(b√6a²)/b=√(b²*6a²)/b=√6a²b
(-6x³√2)/x³=√((-6x³)²*2)/x³=√72x³
-0,(6)a²b√3b=-6/9a²b√3b=√(-6/9*a²b)²*3b=√(4a⁴b³)/3